Dissecting supply chain integration: impact of integration quality on customer-oriented performance. (18th August 2021) - Yang, Chen-Lung; Lin, Shu-Ping; Chan, Ya-Hui; Kim, Myung Kyo; Sheu, Chwen
Abstract : Supply chain integration (SCI) has been touted as an important strategy for obtaining competitive advantage. In the context of the mobile telecommunication service (MTS) industry, this study examines how different dimensions of SCI relate to customer-oriented performance measures, including customer satisfaction, customer relationships, switching costs, and customer loyalty. Building upon the service profit chain framework, this study proposed and tested seven research hypotheses in two dimensions of SCI: upstream (i.e. phone provider and MTS provider) and downstream (i.e. MTS provider and application provider) integrations. As part of these efforts, this study developed a new instrument to measure the quality of upstream and downstream SCIs. The dataset with 158 upstream and 130 downstream integrations in the Taiwanese MTS industry was then analysed by using a structural equation model. The results confirm the impacts of upstream and downstream SCIs on customer loyalty and the mediation effects of relationship quality, customer satisfaction, and switching cost. This study also discovers differential effects of upstream and downstream integrations on customer-oriented performance: the upstream integration serves as an order qualifier in the marketplace, while the downstream integration is the order winner for MTS providers. Several suggestions are made regarding the measurement of SCI and improvement on SCI strategies to achieve customer loyalty in the MTS industry.